2017
DOI: 10.1016/j.cca.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Variation of calcium, copper and iron levels in serum, bile and stone samples of patients having different types of gallstone: A comparative study

Abstract: The higher density and pH of bile, elevated concentrations of transition elements in all types of biological samples (serum, bile and GS), could be an important factor for the formation of different types of GS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Crystal structures and ITC binding of the MNoV P domain with CD300lf showed that either magnesium or calcium can support complex formation. Of particular interest, Ca 2+ is present in high concentrations in bile ( 47 ), making it reasonable to propose that calcium might be present at sites of MNoV infection ( 48 ). It is intriguing to speculate that the availability of divalent cations in the body, which may not be available in the environment, might foster infectivity of the virus once it reaches its target.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures and ITC binding of the MNoV P domain with CD300lf showed that either magnesium or calcium can support complex formation. Of particular interest, Ca 2+ is present in high concentrations in bile ( 47 ), making it reasonable to propose that calcium might be present at sites of MNoV infection ( 48 ). It is intriguing to speculate that the availability of divalent cations in the body, which may not be available in the environment, might foster infectivity of the virus once it reaches its target.…”
Section: Discussionmentioning
confidence: 99%
“…Cu 2+ ions can coordinate with N atoms in the pyrrole ring and lactam ring to form copper bilirubinate complex; meanwhile, under the catalysis of Cu 2+ ion, bilirubin is oxidized by free radicals. Following this, bilirubin is crossed as a polymer with a large conjugated system by Ca bridge, thus creating pigment parts of gallstones with black and deep brown appearance, as can be seen in Figure …”
Section: Resultsmentioning
confidence: 99%
“…The outer parts of gallstones generally have white and yellowish color that indicates the presence of cholesterol, calcium carbonate, and calcium phosphate at this part of the stones. As far as the center part is concerned, the first cholesterol core is formed before Cu 2+ and Ca 2+ ions interact with bile pigment to form calcium/copper bilirubinate . The formation of bilirubinate salts is responsible for the black and brownish color of the central parts of gallstones, which may further triggered by heavy and trace metals for growth of the gallstones.…”
Section: Resultsmentioning
confidence: 99%
“…The sodium bicarbonate cotransporter SLC4A5 plays an important role in the recovery of cerebrospinal fluid pH during hypercapnia-induced acidosis, which can protect the brain from acid damage ( Christensen et al, 2018 ). In gallbladder diseases, some elements in bile (such as Ca 2+ , Fe 3+ , Cu 2+ ) are very significant in the development of GD ( Khan et al, 2017 ). The higher density and pH value of bile and the higher concentration of transition elements may be important factors for the formation of different types of GD.…”
Section: Discussionmentioning
confidence: 99%